The Rise and Fall of CORBA. - Henning, Michi (Communications of the ACM, 2008)
The article discusses the growth and decline in popularity of Common Object Request Broker Architecture (CORBA). A version of CORBA released in 1997 gained wide acceptance among developers building distributed applications. However, a variety of developments served to chip away at CORBA's popularity including the emergence of the Web and the Java programming language. An updated CORBA specification released in 1999 was largely without impact. The author details CORBA's decline and suggests lessons to be learned from it.